Swept-source optical coherence tomography features of regressed macular retinoblastoma - Damodaran, Sourav (Indian J Ophthalmol, 2019)
PURPOSE: To describe the swept-source optical coherence tomography (SS-OCT) features of regressed macular retinoblastoma (RB). METHODS: A cross-sectional observational study was carried out in 13 patients with regressed macular RB with good fixation in at least one eye. Fundus photography and SS-OCT were documented. High-resolution scans with good signal strength were selected. The types of clinical regression and SS-OCT characteristics of the regressed lesions (presence of vitreous detachment, intratumor schisis/cavitation, calcification, foveal dip, and OCT pattern) were noted. RESULTS: Of the 13 eyes, 7 (53%) were group B, 4 (30%) were group C, and 2 (17%) were group D. Lesion involving fovea was seen in seven eyes (53%). On SS-OCT, the lesion was isodense to hyperdense in all cases. Three patterns of regressed RB were noted on OCT. Intralesion calcification was noted in eight cases. Subretinal fluid was not detected in any of the cases. CONCLUSION: SS-OCT is a useful technology to image and analyze cases of regressed macular RB including large lesions. SS-OCT system helps in successful imaging even in smaller children.